The Dynamics and Implications of the Myanmar Civil War: A Conceptual Analysis - Khan, Zarin Tasnim (Academia Journal of Humanities & Social Sciences, 2025)
Myanmar has been struggling with political instability, ethnic tensions, and military rule since its independence in 1948, which culminated in a multidimensional civil war exacerbated by the 2021 coup and public uprisings such as the Spring Revolution. The paper addresses the ethnic tensions, militarisation and mobilisation as the forces behind the conflict and its regional effects. The conceptual framework of Michael E. Brown has been adopted in the paper to analyse the structural, political, economic, and cultural aspects of the discussion using the literature-oriented qualitative technique. The results indicate that the civil war in Myanmar is caused by longstanding ethnic exclusion and concentrated military power, which in turn are compounded by failed democratisation and weak international responses; while suggesting that the functioning of this conflict can hardly be solved without integrative federal reformations, the observance of minority rights and harmonisation of the governing of the regions. This study also explores the spillover impact on the neighbouring states such as Bangladesh, India, China, and Thailand, and explores possible grounds to foster peaceful solutions. By dissecting the conflict in multidimensional terms, the paper aims to contribute to the wider debates of the concept of internal war, ethnic politics, and regional security.